Analysis of Bearing Performance of Monopile and Single Suction Bucket Foundation for Offshore Wind Power under Horizontal Load. (8th June 2022) - Wang, Bin; Qin, Tianqing; Yuan, Changfeng; Li, Liang; Yuan, Minghui; Li, Ying
Abstract : In conjunction with the geological conditions of the East China Sea, the bearing performance of monopile and single-suction bucket foundations is compared and analyzed in shallow and deep-sea conditions under static horizontal loads. Furthermore, the statistical data of wind and wave from 2010 to 2020 in the East China Sea were tabulated into amplitude curves applied to the two foundations in the form of dynamic loads, and the bearing performances of the two foundations under dynamic loads were analyzed. The results show that the typical suction bucket foundation for a wind turbine currently designed in the shallow sea is destabilized under static horizontal loads, while the pile foundation is more stable; both foundations are stable in the deep-sea area. However, the suction bucket foundation displacement is less than the pile foundation. Under dynamic loading, the maximum displacement of monopile in the shallow sea was 127 mm. The maximum displacement of the suction bucket foundation was 434 mm, and the foundation was unstable. Both foundations are stable in deep-sea conditions, and the maximum displacement of the pile foundation is 1.4 times the maximum displacement of the suction bucket. Considering the difficulty construction in the deep sea, it is recommended to use suction bucket foundations.